A broad comparative genomics approach to understanding the pathogenicity of Complex I mutations - Galya V. Klink (Nature Portfolio, 2021)
Abstract Disease caused by mutations of mitochondrial DNA (mtDNA) are highly variable in both presentation and penetrance. Over the last 30 years, clinical recognition of this group of diseases has increased. It has been suggested that haplogroup background could influence the penetrance and presentation of disease-causing mutations; however, to date there is only one well-established example of such an effect: the increased penetrance of two Complex I Leber's hereditary optic neuropathy mutations on a haplogroup J background. This paper conducts the most extensive investigation to date into the importance of haplogroup context in the pathogenicity of mtDNA mutations in Complex I. We searched for proven human point mutations across more than 900 metazoans finding human disease-causing mutations and potential masking variants. We found more than a half of human pathogenic variants as compensated pathogenic deviations (CPD) in at least in one animal species from our multiple sequence alignments. Some variants were found in many species, and some were even the most prevalent amino acids across our dataset. Variants were also found in other primates, and in such cases, we looked for non-human amino acids in sites with high probability to interact with the CPD in folded protein. Using this “local interactions” approach allowed us to find potential masking substitutions in other amino acid sites. We suggest that the masking variants might arise in humans, resulting in variability of mutation effect in our species.